Use of Artificial Intelligence in statistical research - Paul, Ranjit; Arya, Prawin; Kumar, Shiv (Indian Farming, 2019)
Artificial intelligence can be defined as the intelligence exhibited by machines or software. To expand the idea further in simple terms one can, see this as art of making the computers think and act like humans. Activities that can be associated with human thinking, like decision making and learning can be programmed to machines so that they can act like human beings. The process of creating systems that think like humans include cognitive modeling, replicating human thought process and decision making using logical reasoning. Along with thinking, systems behave like humans using natural language processing for communication, storing information effectively and efficiently along with automated reasoning. Due to onset of growing population there arises need for fulfilling demands of billions of people in terms of goods across all the sectors of agriculture. This brings in, the evolving concept of artificial intelligence in use of agriculture to meet demands of future population.